An Analysis of Metaphors in the Other Hands Novel by Chris Cleave - Yuli Yanti; Sufil Lailiyah (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2018)
Metaphor was figurative expression, the transferred sense of physical word, the personification of an abstraction, the application of a word or collocation to what it did not literally denote to describe one thing in terms of another. Metaphor could be found in many media like newspapers, magazines, novels, etc. In this research the researcher indentified the metaphor and described meaning of metaphor in The Other Hands Novel.The data in this research were the sentence that contained metaphor in The Other Hands Novel. This research was done by analyzing the data qualitatively. There was some steps to analyze the data they were: Identifing the sentences in The Other Hands novel, analyzing the metaphors in the sentences to identify the components of metaphor. The researcher defined the source domain and the target domain and analyzed the metaphors in the sentences to find out the literal and non-literal meaning of the metaphor.The findings of the analysis reveal that there were eighteens data of meaning in metaphors found by researcher. The researcher expected the next researchers to do the analysis on metaphors with other object of research. The researcher also expected the next researchers to identify metaphors with different relevant theories.